Pengaruh Fear of Missing Out (FOMO) dan Konformitas Sosial terhadap Keputusan Pembelian Produk Blind Box Pop Mart pada Konsumen di Kota Manado: Indonesia - Anggun Therok; Fitayantri Tamau (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the influence of Fear of Missing Out (FOMO) and Social Conformity on purchase decisions for Pop Mart Blind Box products among consumers in Manado City. Grounded in the Theory of Planned Behavior (TPB), this research adopts a quantitative, descriptive–explanatory design. Data were collected from 150 respondents selected through purposive sampling via an online questionnaire employing a five-point Likert scale. Multiple linear regression was applied to test the research hypotheses. The results demonstrate that both FOMO (β = 0.412; t = 5.821; p < 0.001) and Social Conformity (β = 0.378; t = 5.214; p < 0.001) positively and significantly influence purchase decisions, with both variables collectively explaining 56.3% of the variance (R² = 0.563). These findings indicate that the psychological urgency induced by FOMO and the normative social pressure from conformity behavior are key drivers of blind box purchasing among young consumers in Manado. Managerially, the results suggest that marketing strategies emphasizing product scarcity, limited-edition releases, and community-based social validation are highly effective within this product category. This study contributes to the growing body of literature on hedonic and impulsive consumption behavior in the context of novelty retail products in Indonesia.